Cultural Study on Domestic Violence in Batak Community - Alesyanti, Alesyanti (Italian Sociological Review, 2019)
Many practical conflicts rise within societies these days. These has caused some intrusion to the people life. Based on my observations and predictions, this happened due to a lack of understanding about the culture, behavior, personalities, customs, and regulation which govern us all. Human being has been equipped to function by upholding the certain cultures values. That values, which must be up hold in particular society, may not be considered important by other communities; worse, sometimes it is even considered a deviant act. Cultural values covered various aspects of social norms, that is taught to every individual within community that can serve as guidelines when performing various roles in different social situations. Social norms partly incorporated in relation to the other, and emerged as a social institution which guide the demands of society, or in accordance with the idealized way of life portrayed in the group. This ideal viewpoint forms sanctuary and corridor which must not be disrupted but need to preserve. This research aims to determine familial pattern adopted, wife status, and Batak culture which provides opportunities for violence against wives in Batak household, and to analyze forms of domestic violence in Batak community that lead to legal problems.